A possible Cambrian stem-group gnathiferan-chaetognath from the Weeks Formation (Miaolingian) of Utah. (July 2020) - Conway Morris, Simon; Smith, Ru D.A.; Cuthill, Jennifer F. Hoyal; Bonino, Enrico; Lerosey-Aubril, Rudy
Abstract: In recent years the plethora of 'weird wonders, ' the vernacular for the apparently extinct major body plans documented in many of the Cambrian Lagerstätten, has been dramatically trimmed. This is because various taxa have been either assigned to known phyla or accommodated in larger monophyletic assemblages. Nevertheless, a number of Cambrian taxa retain their enigmatic status. To this intriguing roster we add Dakorhachis thambus n. gen. n. sp. from the Miaolingian (Guzhangian) Weeks Formation Konservat-Lagerstätte of Utah. Specimens consist of an elongate body that lacks appendages but is apparently segmented. A prominent feeding apparatus consists of a circlet of triangular teeth, while posteriorly there are three distinct skeletal components. D. thambus is interpreted as an ambush predator and may have been partially infaunal. The wider affinities of this new taxon remain conjectural, but it is suggested that it may represent a stem-group member of the Gnathifera, today represented by the gnathostomulids, micrognathozoans, and rotifers and possibly with links to the chaetognaths. UUID: http://zoobank.org/22113e6b-f79e-4d06-9483-144618a61327